Determination of Trace Elements in Edible Nuts in the Beijing Market by ICP-MS - YIN, Liang Liang; TIAN, Qing; SHAO, Xian Zhang; KONG, Xiang Yin; JI, Yan Qin (Biomedical and environmental sciences, 2015)
Nuts have received increased attention from the public in recent years as important sources of some essential elements, and information on the levels of elements in edible nuts is useful to consumers. Determination of the elemental distributions in nuts is not only necessary in evaluating the total dietary intake of the essential elements, but also useful in detecting heavy metal contamination in food. The aim of this study was to determine the mineral contents in edible nuts, and to assess the food safety of nuts in the Beijing market. Levels of Li, Cr, Mn, Co, Cu, Zn, As, Se, Rb, Sr, Mo, Cd, Cs, Ba, Pb, Th, and U in 11 types of edible nuts and seeds （macadamia nuts, lotus nuts, pistachios, sunflower seeds, pine nuts, almonds, walnuts, chestnuts, hazelnuts, cashews, and ginkgo nuts） as well as raisins were determined by inductively coupled plasma mass spectrometry （ICP-MS）. The accuracy of the method was validated using standard reference materials GBWlO014 （cabbage） and GBWlO016 （tea）. Our results provide useful information for evaluating the levels of trace elements in edible nuts in the Beijing market, will be helpful for improving food safety, and will aid in better protecting consumer interests.